Features of adaptation of foreign students to the Russian linguo-cultural and educational environment - Nina Leonidovna Fedotova; Lyudmila Vladimirovna Miller (Rusistika (Moskva. Online), 2018)
The article describes the factors that influence the processes of socio-psychological and sociocultural adaptation of foreign students receiving education in a second language in terms of the culturally alien environment. The adaptation process is considered in two interrelated coordinate systems: the student - his/her socio-cultural environment and student - educational environment, in which he included natural way. Socio-cultural adaptation of a foreign student is a multi-step process that includes: 1) dosed directly related to the motivational sphere of the student’s receipt of information about the culture of the country of the target language; 2) development of the ability to correct interpretation of specific manifestations of communicative behavior of Russian; 3) the formation of practical skills of educational professional and cultural-everyday communication with Russians. The authors substantiate the position that the process will be less painful and more effective if: a) to make it manageable; b) to develop a set of measures to prevent failures in communication and to remove the psychological tension, which is due to the influence of other cultures.